The Doctrine of Faith, Doubt, and Assurance: A Historical, Philosophical, and Theological Analysis - Strehle, Stephen (Religions, 2024)
How do individuals find assurance of their personal standing before God? This article discusses the way different traditions of the Christian faith tried to answer the question—some leaving room for doubt in the process and others demanding absolute certainty from the believer. All fellowships experienced some problems with the issue due to the very nature of the question. Assurance required a reflexive act that turned the eyes of the believer away from the good things of God and the promises of the gospel toward an inspection of one’s inner man and motives that were difficult to discern. Those fellowships that emphasized a human condition in the process of salvation or assurance often struggled with their depravity before God and unworthiness to claim the promises of divine grace. This paper particularly focuses upon the struggles of the so-called Calvinists, who were more enamored with the question than the other fellowships and had difficulty developing a coherent or definitive answer, caught as they were between tensions in their theology, between the Christocentric vision of John Calvin that led toward assurance and the synergistic tendences of Theodore Beza and Heinrich Bullinger that led toward doubt. The paper provides some criticism of their theology but sympathizes with their struggle and finds faith and doubt inevitable parts of the Christian life here on earth.